2016
DOI: 10.1016/j.paid.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Is emotional impulsiveness (Urgency) a core feature of severe personality disorder?

Abstract: Recent literature has focused on severity of personality disorder (PD) and a trait-based assessment of PDs in preference to assessment by specific sets of diagnostic criteria. Evidence suggests that emotional impulsiveness, also known as Urgency (Whiteside SP, Lynam DR. The five factor model and impulsivity: using a structural model of personality to understand impulsivity. Personality and Individual Differences,30, 669-689, 2001) might contribute to a broad spectrum of PDs and to overall PD severity. In a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(31 reference statements)
2
12
0
Order By: Relevance
“…Students with higher Cluster B personality disorder symptoms were more likely to demonstrate CBP. This result may be explained by the studies that have reported significant associations of different personality disorders with different negative factors that may lead to CBP such as violent behavior (Garofalo and Wright 2017;Howard 2015;Ostrowsky 2010), emotional impulsiveness (Howard and Khalifa 2016), neuroticism, disagreeableness (Watson 1998), antagonism, psychoticism (Hopwood et al 2013), aggression, anger, hostility (Velotti et al 2016), and higher risk of psychological violence (Ten Have et al 2014). Recent studies also demonstrate that cyberbullying is associated with psychopathological traits (Aboujaoude et al 2015;Floros et al 2013;Kokkinos et al 2014), and the dark triad (Baughman et al 2012;Goodboy and Martin 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with higher Cluster B personality disorder symptoms were more likely to demonstrate CBP. This result may be explained by the studies that have reported significant associations of different personality disorders with different negative factors that may lead to CBP such as violent behavior (Garofalo and Wright 2017;Howard 2015;Ostrowsky 2010), emotional impulsiveness (Howard and Khalifa 2016), neuroticism, disagreeableness (Watson 1998), antagonism, psychoticism (Hopwood et al 2013), aggression, anger, hostility (Velotti et al 2016), and higher risk of psychological violence (Ten Have et al 2014). Recent studies also demonstrate that cyberbullying is associated with psychopathological traits (Aboujaoude et al 2015;Floros et al 2013;Kokkinos et al 2014), and the dark triad (Baughman et al 2012;Goodboy and Martin 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that individuals with Cluster B traits are more violent (Garofalo and Wright 2017;Howard 2015;Ostrowsky 2010), emotionally impulsive (Howard and Khalifa 2016), antagonist, psychotic (Hopwood et al 2013), aggressive, angry, hostile (Velotti et al 2016), and have a higher risk of psychological violence (Ten Have et al 2014). Given that these emotional, psychological, and personality features are important predictors of CBP, it can be expected that individuals higher on Cluster B traits will more likely demonstrate CBP.…”
Section: The Mediating Role Of Cluster B Personality Traitsmentioning
confidence: 99%
“…Third, we found a significant correlation between inadequate response inhibition and antisocial PD, which is in line with research showing antisocial PD is characterized by "increased rapid-response impulsivity" (Swann, Lijffijt, Lane, Steinberg, & Moeller, 2009, p. 1) and recent research showing a relationship between PD severity and urgency facet, which equals our response inhibition dimension (Howard & Khalifa, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…A recent study of personality disordered offenders [26] confirmed that severity of personality disorder measured either by combining externalizing and externalizing features or by aggregating across dimensional scores of individual personality disorders, was associated with a high level of negative Urgency. Of all the UPPS scales, only Urgency was able to predict severity of personality disorder.…”
Section: Emotional Impulsiveness Is a Core Feature Of Severe Personalmentioning
confidence: 91%